Cap‐Score™ prospectively predicts probability of pregnancy. Issue 8 (25th September 2018) - Schinfeld, Jay; Sharara, Fady; Morris, Randy; Palermo, Gianpiero D.; Rosenwaks, Zev; Seaman, Eric; Hirshberg, Steve; Cook, John; Cardona, Cristina; Ostermeier, G. Charles; Travis, Alexander J.
Abstract : Semen analysis (SA) poorly predicts male fertility, because it does not assess sperm fertilizing ability. The percentage of capacitated sperm determined by GM1 localization ("Cap‐Score™"), differs between cohorts of fertile and potentially infertile men, and retrospectively, between men conceiving or failing to conceive by intrauterine insemination (IUI). Here, we prospectively tested whether Cap‐Score can predict male fertility with the outcome being clinical pregnancy within ≤3 IUI cycles. Cap‐Score and SA were performed ( n  = 208) with outcomes initially available for 91 men. Men were predicted to have either low ( n  = 47) or high ( n  = 44) chance of generating pregnancy using previously‐defined Cap‐Score reference ranges. Absolute and cumulative pregnancy rates were reduced in men predicted to have low pregnancy rates versus high ([absolute: 10.6% vs. 29.5%; p  = 0.04]; [cumulative: 4.3% vs. 18.2%, 9.9% vs. 29.1%, and 14.0% vs. 32.8% for cycles 1–3; n  = 91, 64, and 41; p  = 0.02]). Only Cap‐Score, not male/female age or SA results, differed significantly between outcome groups. Logistic regression evaluated Cap‐Score and SA results relative to the probability of generating pregnancy (PGP) for men who were successful in, or completed, three IUI cycles ( n  = 57). Cap‐Score was significantly related to PGP ( p  = 0.01). The model fit was then tested with 67 additional patients ( n  = 124; five clinics); the equation changed minimally, but fit improved ( p  < 0.001; margin of error: 4%). The Akaike Information Criterion found the best model used Cap‐Score as the only predictor. These data show that Cap‐Score provides a practical, predictive assessment of male fertility, with applications in assisted reproduction and treatment of male infertility. Abstract : This study prospectively demonstrated that the absolute pregnancy rate of men with normal Cap‐Scores™ was 278% greater than those predicted to have difficulty conceiving due to low Cap‐Scores. On the first IUI attempt, the difference was even greater—423%. In addition, logistic regression analysis showed that Cap‐Score alone was predictive of pregnancy outcome and defined the association between Cap‐Score and the probability of men to generate pregnancy.